25.0k views
4 votes
The midpoint (x, y) and the end point (x2, y2) are known. Find (x1, Y1) using the midpoint formula.

a. (x1,y1) = (2x + x2, 2y+y2)

b. (x1,y1) = (2x - x2, 2y - y2)

c. (x1,y1) = (x + x2, y + y2)

d. (x1,y1) = (x - x2, y - y2)

User Naraen
by
5.6k points

1 Answer

2 votes

Answer:

(x1,y1) = (2x - x2, 2y - y2)

Explanation:

Given:

Midpoint = (x , y)

End point = (x2, y2)

Find:

(x1, y1)

Computation:

Mid-point formula

x = (x1 + x2) / 2 , y = (y1 + y2) / 2

So,

2x = x1 + x2 , 2y = y1 + y2

x1 = 2x - x2 , y1 = 2y - y2

So,

(x1,y1) = (2x - x2, 2y - y2)

User Pchajer
by
4.4k points